My own true name : new and selected poems for young adults, 1984-1999 - Mora, Pat (Piñata Books, Arte Público Press, 2000)
More than sixty poems, some with Spanish translations, include such titles as "The Young Sor Juana," "Graduation Morning," "Border Town 1938," "Legal Alien," "Abuelita Magic," and "In the Blood."